2018
DOI: 10.1186/s12879-018-3079-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an optimized manufacturing process for inactivated quadrivalent influenza vaccine: a phase III, randomized, double-blind, safety and immunogenicity study in children and adults

Abstract: BackgroundGSK has modified the licensed monovalent bulk manufacturing process for its split-virion inactivated quadrivalent influenza vaccine (IIV4) to harmonize the process among different strains, resulting in an increased number of finished vaccine doses, while compensating for the change from inactivated trivalent influenza vaccine (IIV3) to IIV4. To confirm the manufacturing changes do not alter the profile of the vaccine, a clinical trial was conducted to compare IIV4 made by the currently licensed proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The frequency of reported fever in children aged 6 months–8 years in this current passive ESS study was comparable to that reported in clinical trials [ 21 , 23 ]. However, it should be cautiously interpreted since the fever ≥ 38 °C was self-reported by parents in the current study, and we did not have the chance to assess the start and end date of fever during the first 7 days post vaccination.…”
Section: Discussionsupporting
confidence: 86%
“…The frequency of reported fever in children aged 6 months–8 years in this current passive ESS study was comparable to that reported in clinical trials [ 21 , 23 ]. However, it should be cautiously interpreted since the fever ≥ 38 °C was self-reported by parents in the current study, and we did not have the chance to assess the start and end date of fever during the first 7 days post vaccination.…”
Section: Discussionsupporting
confidence: 86%
“…The SIV vaccines with improved safety has been used as a commercial seasonal influenza virus vaccine for decades and is safe and effective in most populations (18). However, the SIV vaccine is not as effective in children and the elderly (21,37,38). The reduced vaccine effectiveness elicited by SIV vaccines compared to WIV vaccines was also observed in this study.…”
Section: Discussionsupporting
confidence: 58%
“…The clinical trials included [25][26][27][28][29][30][31][32] and the number of participants is shown in Table 1. Demographic characteristics and prevaccination seropositivity for HI against the vaccine homologous virus and the A/H1N1pdm09 virus are shown in Supplementary Tables 1 and 2, respectively. ELISA Anti-H1 stalk antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…6; Table 1; Supplementary Table 6). [25][26][27][28][29][30][31][32] We aimed to select approximately 30 participants from the relevant treatment groups of each trial. Participants were eligible for the present study if they had completed the clinical trial according to the protocol and had sufficient residual sample volume at all protocol-specified sample timepoints.…”
Section: Clinical Trials Participants and Vaccinesmentioning
confidence: 99%